Effect of Local Anesthesia on Pain During Arterial Puncture: The GAEL Randomized Placebo-Controlled Trial - Beaumont, Marc; Goret, Marion; Orione, Charles; Fauche, Alexandre; Nowak, Emmanel; Dion, Angelina; Darnois, Veronique; Tromeur, Cecile; Cogulet, Virginie; Leroyer, Christophe; Couturaud, Francis; Le Mao, Raphael (Respiratory care, 2021)
Arterial puncture is often painful for patients. The aim of this study was to compare use of local anesthesia as a eutectic mixture of 2 local anesthetics, lidocaine and prilocaine, versus placebo. We conducted a double-blind, randomized controlled trial. Subjects were eligible if arterial puncture was indicated. The primary outcome was an experienced pain > 2 on a numerical pain rating scale. As having had a previous experience of arterial puncture was expected to be predictive of the current response, we planned 3 comparisons between use of local anesthesia and placebo: in the whole sample, among subjects with a painful previous experience, and among subjects with a painless previous experience. Multiple testing was analyzed using the Bonferroni correction for the primary outcome. The secondary outcome was the numerical pain rating scale score itself. All analyses were performed on an intention-to-treat basis. A total of 136 subjects were included in this study. The primary outcome occurred in 20.9% in the active arm versus 37.7% in the placebo arm in the whole sample (relative risk 0.55; 95% CI when adjusting for multiple testing ranged was 0.28-1.09, = .10; 95% CI without adjustment was 0.32-0.97, = .038). No significant heterogeneity in the study treatment effect was found when considering previous painful or painless arterial puncture ( = .70). The numerical pain rating scale score was 1.55 ± 2.03 in active group versus 2.09 ± 2.15 in the placebo group ( = .13). We found that application of a eutectic mixture reduced the number of painful arterial punctures by 50% compared with placebo. However, this result was not statistically significant. (ClinicalTrials.gov registration NCT01964248.).